If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y+6=90
We move all terms to the left:
6y+6-(90)=0
We add all the numbers together, and all the variables
6y-84=0
We move all terms containing y to the left, all other terms to the right
6y=84
y=84/6
y=14
| v-4.6=9.8 | | 3y-1=-5(-3+y) | | 6-3d=-3(d-2) | | 0.4x+1.6=0.8x-0.4 | | -3x=8x+434 | | 5x+4(x+1)=x | | 1+7n=9+5n | | 9(n=+3)-10(n-5)=27 | | -8g+7=-33 | | .-6x+2=6x-70 | | 3/20=p/100 | | 12x-5=6x | | m+22=43 | | 6n-2=(n-3 | | 45=-5h | | 5b–11=2 | | -3(x-4)+5x=10 | | 2n-10=-4 | | -(10-x)=7 | | 6(4n+3)=-174 | | 17-61=25-3r | | 4/3x−5/6=52 | | -8x+6(x+8=38 | | 17a-33=1 | | 5-6(a+12)=7+a | | 14/x+6=7/4 | | 9+g=-17 | | 3k-2k=2k-5-4K | | 6+4x=-x+6 | | –11=24+–5v | | (1/3)-x=(-1/2) | | 3x+2=4x–93.5x–8= |